The Role Of Job Satisfaction As A Mediating Variable On The Effect Of Reward And Work-Life Balance On Employee Retention - Icknaton Icknaton; Suhana Suhana (Publikasi Indonesia, 2025)
This study aims to analyze the effect of reward and work life balance on employee retention both directly and indirectly through job satisfaction as mediation. The population used in this study is all employees working at the Genuk District Office, Semarang City, which totals 94 employees. The sampling technique is the census method or saturated samples. Thus, the number of samples used was 94 respondents. The data source used was primary data, with a questionnaire data collection method. The data analysis technique used is Structural Equation Modeling-Partial Least Square (SEM-PLS) version 3. The results of the study show that rewards have a positive and significant effect on job satisfaction, and work life balance has a positive and significant effect on job satisfaction. Rewards have a positive and significant effect on employee retention, work life balance has a positive and significant effect on employee retention, and job satisfaction has a positive and significant effect on employee retention. The results of the mediation test were obtained that job satisfaction can mediate the effect of rewards on employee retention, and job satisfaction can mediate the effect of work life balance on employee retention. This research has both theoretical and practical implications.